Cultivating Charismatic Power Islamic Leadership Practice in China - Cone, Tiffany (Springer International Publishing, 2018)
Islam and China are topics of relevance and contention in today's economic, political and religious climate. In this work, Tiffany Cone makes an important contribution to these contemporary discourses through an ethnographic case study of Islamic leadership and the cultivation of charismatic power by Sufi disciples at a shrine site in Northwest China. Though this volume focuses on a specific religious community, it carries valuable insights into religious unity, syncretism and religious legitimacy, materialism and religious integrity, and the stability of religious institutions in light of rapid economic growth. Cultivating Charismatic Power speaks to global concerns about the rise of a militant Islam and an increasingly aggressive Chinese State. As such, it will appeal to scholars and practitioners across a range of fields including anthropology, philosophy, religious studies, Islamic Studies, and Chinese Studies.